The Trajectory of the Landscape and Functionality of Urban Watercourses: A Study of Lavras City, Brazil - Sousa, Rafael de Brito; Paiva, Patrícia Duarte de Oliveira; Reis, Michele Valquíra dos; Carcaud, Nathalie (Frontiers in Sustainable Cities, 2022)
The growth of the urban population promotes a strong pressure to occupy open spaces in urban center, including around watercourses. Canalization and drainage techniques favored urban expansion and occupation of these spaces. In long term, this has not been efficient, since it is not a sustainable decision, mainly in view of the challenges provided by climate change. The purpose of this work was to analyze the modification of the landscape and multifunctionality of the urban watercourses in relation to socioeconomic and environmental scope of the evolution of an urban area using Lavras city, Brazil, as model. For that, city's hydrographic grid was drawn from the digital elevation model (DEM) corrected by manual vectorization after field visits and analysis of high-resolution images. To understand natural and sociocultural evolution processes, a compilation of geo-historical information about the origin and formation of the city was made using Patchwork Quilt methodology. To understand the actions and perceptions of different actors from urban watercourses in Lavras, questionnaires were applied to the population, and interviews were directed to the public and private managers. It was observed that the watercourses and their surroundings lost a large part of their natural, social, and economic functions, after the 1980s, only having a drainage function. The areas in expansion prioritize the natural function preservation but lack the incentive to implement the other functions such as social and economic. With the economic valuation of land, the implementation of green and blue infrastructure has not yet been prioritized. Even with the legislation that provides multifunctional uses for rivers and their banks, the urban watercourses from Lavras remained largely monofunctional. This did not contribute to increasing the city's green areas and the reintegration of watercourses into the urban landscape. The population values the water present in the urban landscape and yearns for multifunctional solutions such as green areas and urban gardens. Public and private actors recognize the lack of clarity in the legislation, and in the definition of concepts and techniques to be adopted. Multifunctional solutions can be in favor of reconciling different interests, promoting the reintegration of rivers into the urban landscape.